The politics of sexuality: Alternative visions of sex and social change - Phoenix, Jo (2017)
This chapter presents a brief overview of criminology's early focus on female prostitution before delineating four contrasting visions of sex and social change in late modernity. It aims only to show how the critical interrogation of sexual politics has been dominated by the three following questions: what is normal sex? What determines the definitional boundaries between permitted and unpermitted sexualities? Who are the winners and losers in normal and abnormal sexual transactions? In many countries, the last 15 years has been a period of extraordinary reform to criminal and civil law concerning LGBTQ people. In the Republic of Ireland, a series of criminal cases in the late 1990s and government inquiries in the opening decade of the twenty-first century demonstrated that hundreds of children had been subjected to sexual abuse by clerics in the previous decades. The main task of criminologists is to provide ever-alternative analyses of the social, cultural and economic conditions